Assessment of Volatile Oil Composition, Phenolics and Antioxidant Activity of Bay (Laurus nobilis) Leaf and Usage in Cosmetic Applications - Şeyda KIVRAK; Tolga GÖKTÜRK; İbrahim KIVRAK (International Journal of Secondary Metabolite)
In this study, the components of the volatile oil obtained from Laurus nobilis leaves by steam distillation were determined using Agilent 6890 Gas Chromatography (GC) - 5975 Mass Spectrometry (MS). The antioxidant activities of different extracts of L. nobilis leaves were determined by using DPPH• (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity, β-carotene-linoleic acid bleaching assay and ABTS•+ (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) cation radical decolorization assay. Determination of the total phenolic contents of L. nobilis leaf extracts were performed using the Folin-Ciocalteau procedure and total flavonoid contents were measured using a spectrophotometric assay. According to the GC/MS results, 1,8-cineole (46.16%), alpha-terpinyl acetate (10.62%), alpha-pinene (6.27%), terpinen-4-ol (5.07%) and sabinene (4.99%) were found to be the major compounds in volatile oil. The obtained volatile oil was used to make skin care lotion. Stability tests and organoleptic analyses of final product were performed after 1, 5, 30 and 90 days of production. The highest amounts of total flavonoid content were found to be 5.48 ± 0.65 and 8.60 ± 0.12 µg QEs/mg in ethyl acetate and ethanol extracts, respectively. The highest amounts of total phenolic compounds were found to be 54.42 ± 0.14 and 25.32 ± 0.10 µg PEs/mg in ethyl acetate and ethanol extracts, respectively. According to the results of ABTS•+, DPPH• and β-carotene linoleic acid assays, ethyl acetate extract was found to be the most active extract (24.98±0.87 µg mL-1, 75.65±0.77 µg mL-1 and 19.32±1.04 µg mL-1).